2022
DOI: 10.3390/healthcare10030416
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Faculty and Peer Mentoring to Promote Social Belonging among Minoritized Physical Therapist and Nursing Students

Abstract: Minoritized health sciences students report experiencing social isolation and discrimination, and cite the lack of faculty representation as barriers to their success. While virtual mentoring can increase sense of belonging and connectedness, these effects have not been examined in minoritized health sciences students. The purpose of this study was to investigate whether virtual mentoring from faculty and peers could decrease social isolation and promote social belonging among minoritized first-year physical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…Consistent with existing research, [5][6][7][8][9]22 CLD learners expressed challenges in the CEE, including encountering biased patients and feeling pressure to assimilate into American culture. CLD mentors experienced similar challenges early in their careers.…”
Section: Cld Student Outcomesmentioning
confidence: 76%
See 3 more Smart Citations
“…Consistent with existing research, [5][6][7][8][9]22 CLD learners expressed challenges in the CEE, including encountering biased patients and feeling pressure to assimilate into American culture. CLD mentors experienced similar challenges early in their careers.…”
Section: Cld Student Outcomesmentioning
confidence: 76%
“…15 When this program was replicated in the virtual environment with DPT and nursing faculty, all members of the mentoring team once again made gains. 22 Reichard et al 20 conducted cross-cultural training for participants in the US and South Africa and found a significant increase in CC PsyCap and cultural intelligence post-training. In this study, all three CIs gained CC PsyCap over the course of the study reinforcing that this resource can be developed by sharing knowledge and offering the opportunity for skill development.…”
Section: Theme 1: Pts From Minoritized Backgrounds Have a Unique Soci...mentioning
confidence: 99%
See 2 more Smart Citations
“…Mentorship programs are a well-established method of increasing students' and practitioners' self-efficacy, practical skills, and therapeutic use of self (Braveman, 2006). Naidoo et al (2022) asserted that physical therapy and nursing mentors serve as role models who have overcome barriers through perseverance; this can improve mentee confidence while decreasing feelings of isolation. Additionally, Ford et al (2020) found that 83% of occupational therapy students from marginalized communities expressed the desire to have a mentor with shared experiences.…”
Section: Introductionmentioning
confidence: 99%